Pesan Islam Melalui Radio - Fahridads, Hanif; Chakim, Sulkhan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2018)
This article examines Islamic material or message broadcast by Radio Republik Indonesia (RRI) through â€œMutiara Pagiâ€ program which is focused on reception of listeners in Banyumas Regency. The mass media is not only a tool for disseminating information in all parts of the earth, but also a tool for organizing the agenda, as well as telling people what is important and not. Audience is not merely passive but seen as a cultural agent which has its own power in terms of generating meaning from various discourses offered by the media. The meaning of the media can be open or polysemic and can even be responded by the opposition by the audience. This review contributes to strengthening and developing locally-based broadcasting content. The focus of this study is how reception of Radio Program listeners 'mutiara pagi'. Data collection methods used are forum group discussion (FGD), in-depth interview to get data. While the data analysis is used by analysis of reception. The findings of this study reinforce morley's opinion that explains the three positions related to the meaning of audiences against media messages. These three positions include dominant positions that illustrate that viewers accept, while the negotiable position illustrates that the viewers partly accept partially reject or even criticize the message of â€œmutiara pagiâ€ program. The audience is partially opposed or refused altogether.